Identifikasi Potensi Bahaya Menggunakan Metode Job Safety Analysis Di PT. SP Alumunium: Identifikasi Potensi Bahaya Menggunakan Metode Job Safety Analysis Di PT. SP Alumunium - Wirazahrawan, Adib Priyahita (Universitas Duta Bangsa Surakarta, 2024)
PT. SP Alumunium is a company that produces cooking utensils such as pots, pans and others using raw materials used are pure aluminum and used aluminum which is melted and then molded into the desired product. Initial observations show that workers in doing their work pay less attention to occupational safety and health. The purpose of this study is to analyze the implementation of K3 at PT. SP, and identify potential hazards especially in the type of aluminum melting and molding work at PT. SP Alumunium. The method used related to the existing problems is by using the Job Safety Analysis (JSA) method. This method focuses on identifying hazards related to the tasks / jobs performed. JSA steps are; Describe the tasks / jobs in sequence, identify hazards at each step that can interfere with K3, conduct a risk assessment by estimating the likelihood and consequences, provide recommendations and implement risk reduction steps. The results of JSA in the melting and molding work process each have four (4) work activities. Potential hazards that may occur are physical hazards such as exposure to heat, repetitive work; ergonomic hazards such as hand and waist injuries; chemical hazards such as exposure to combustion smoke. Hazard control that can be done by using safety shoes and gloves, improving work posture when lifting to avoid injury, using masks in the melting section. The conclusion obtained is that the implementation of K3 at PT. SP Alumunium has not been running well, it is seen that there is no special team that handles K3. While the potential hazards in the melting and molding process include potential physical hazards, ergonomic hazards, and chemical hazards